Seamless Solar-Powered Hydroponics Revolutionizes Urban Farming in Indonesia: Hidroponik Bertenaga Surya Tanpa Batas Merevolusi Pertanian Perkotaan di Indonesia - Muchtarom, Alfin; Jamaluddin, Jamaluddin (Indonesian Journal of Innovation Studies, 2024)
This study explores the use of PLTS (solar power) as an alternative energy source for urban hydroponic systems. Due to PLTS's limited capacity, an automatic transfer switch (ATS) is utilized to seamlessly switch between PLTS and PLN (public electricity) based on sensor readings. The system uses an INA219 sensor to monitor PLTS voltage, a TDS sensor for water quality, and a NodeMCU microcontroller, with data displayed on an LCD and Blynk for remote monitoring. Testing showed a PLTS voltage of 12.0V, with sensor accuracies of 96% (INA219) and 98.59% (TDS). Overall, the system demonstrated reliable and optimal performance, providing a sustainable solution for urban hydroponic farming. Highlights: 1. PLTS and PLN integration ensures reliable power for urban hydroponics.2. High sensor accuracy supports precise system monitoring.3. Remote monitoring via LCD and Blynk enhances control and sustainability. Keywords: PLTS, hydroponic systems, automatic transfer switch, NodeMCU, sustainability